Ensino por investigação na educação financeira mediado pelas tecnologias digitais - Biava, Muana (2024)
The dissertation consists of an investigative study in the professional master's degree in Science and Mathematics Teaching of the Graduate Program in Science and Mathematics Teaching (PPGECM) of the University of Passo Fundo (UPF), research line "Pedagogical Innovations for the teaching of Science and Mathematics". The theme involves financial education through Inquiry-Based Teaching mediated by digital technologies in Basic Education. Faced with the problem of the lack of effective teaching materials aligned with current tools, in addition to the consequences resulting from the lack of financial management of Brazilian families, such as the indebtedness that causes a large part of them, the proposal was to analyze the results of the application of an educational product that follows the precepts of inquiry-based teaching, which uses technology as a basic tool to enhance the concepts of financial education. The study is based on the development of the stages described by Pedaste (2015), which are: orientation, conceptualization, investigation, conclusion, and discussion. Thus, an educational product was built with different stages and descriptions to be applied, making room for digital technologies. In methodological terms, the research is qualitative in nature, conducted through data collection during the application of the educational product, through logbooks, student feedback, and an online portfolio of activities. Regarding the concept of financial education adopted, the Bahamas (2020) proposal, known as "4 Rs" (Recognize, Review, Record, and Perform), was emphasized. The application of the product lasted three weeks, being completed in 12 meetings, with students aged 13 to 15 from the eighth grade class of the Salto Veloso Integrated Education Center (CMEISV), located in the city of Salto Veloso, in the midwest region of Santa Catarina. Based on the data produced, two categories of analysis were analyzed: "feedback and reflections" and "student engagement, socialization and participation". The results indicated greater interactivity of students with the activities presented, use of technologies and social media, and practical experience through participatory dynamics in the community. This material, together with the results presented, is available for free access on the program's website (https://www.upf.br/ppgecm/dissertacoes-e-teses/dissertacoes), on the PPGECM educational products website (https://www.upf.br/produtoseducacionais) and on the EduCapes Portal (http://educapes.capes.gov.br/handle/capes/748734).